Diagnostic Study of Public Financial Management : To Strengthen Health Financing and Service Delivery in Bangladesh - Ahmed, Shakil; Begum, Tahmina; Smith, Owen (World Bank, Washington, DC, 2019)
Robust public financial management (PFM) systems are crucial to ensure the efficacy and integrity of public health spending, thereby contributing to improved service coverage and financial protection, as required for achieving universal health coverage. A weak PFM system has impeded implementation of the Bangladesh health care financing strategy 2012-2032. This paper aims to identify and document major PFM challenges in relation to the interventions outlined in this strategy document, on the grounds that relaxing these constraints will strengthen implementation. Further, the study examines PFM barriers in service delivery, such as delays in fund availability and procurement and the lack of operational funds at the facility level. The paper points to a number of obstacles, including the absence of a legal framework for implementing a social health protection scheme, no laws to retain user fees at health facilities or to change financial rules to introduce flexible cash at facilities, district health managers without delegated financial power, noncompliance with audit observations, and need for PFM capacity strengthening. Short-, medium- and long-term actions are presented to address these PFM issues. Removing these barriers will not require significant additional resources, but will offer the potential to significantly enhance value for money for Bangladesh’s government health budget.